The gendered impacts of the COVID-19 pandemic in Kenya, Niger, Rwanda, and Uganda: Evidence from phone surveys - Bryan, Elizabeth; Mawia, Harriet; Ringler, Claudia; Mane, Erdgin; Costa, Valentina; Ndoro, Rumbidzai (International Food Policy Research Institute, 2023)
The COVID-19 pandemic has had far-reaching impacts in every part of the world, including on vulnerable populations in rural areas of low- and middle-income countries. This report explores the ways in which men and women in rural areas of four countries in sub-Saharan Africa (SSA)—Kenya, Niger, Rwanda, and Uganda—experienced the COVID-19 pandemic and associated income losses, as well as their responses to the crisis. To identify and monitor the differential effects of the COVID-19 pandemic on women and men in rural households, IFPRI conducted phone surveys in selected regions of the four focal countries, with financial and technical support from the Food and Agriculture Organization of the United Nations (FAO). The surveys traced gender differences in responses to the pandemic and associated restrictions, such as choice of coping strategies, access to public assistance, and changes in the care burden for men and women.